Impact of mixed lignocellulosic substrate and fungal consortia to enhance cellulase production and its application in NiFe2O4 nanoparticles mediated enzymatic hydrolysis of wheat straw - Srivastava N.; Singh R.; Srivastava M.; Syed A.; Bahadur Pal D.; Bahkali A.H.; Mishra P.K.; Gupta V.K. (My University, 2025)
Economic biowaste to biofuels production technology suffers from issues including high production cost of cellulase enzyme and its low efficiency. In this study five lignocellulosic biomass based on their high cellulosic contents are employed in 1:1 ratio with mixed fungal consortia to achieve enhance cellulase production via solid state fermentation. Under the optimum condition total 41 IU/gds FP activity was achieved in 120 h at 40 °C and pH 6.0. Further, crude cellulase was evaluated to improve thermal and pH stability under the influence of 2.0 mg/L NiFe2O4 nanoparticles, showed stability at 70 °C and pH 6.0 up to 8 h. Consequently, NiFe2O4 nanoparticles treated cellulase was used for the enzymatic hydrolysis of alkali treated wheat straw, and total 53 g/L reducing sugars could be produced in 18 h at 65 °C and pH 6.0. Thus, nanoparticles mediated enzymatic hydrolysis exhibited ∼ 29% and ∼ 28% higher sugar yield and productivity as compared to control after 18 h. © 2021 Elsevier Ltd